2014
DOI: 10.1111/josh.12154
|View full text |Cite
|
Sign up to set email alerts
|

Organized Extracurricular Activities: Are In‐School and Out‐of‐School Activities Associated With Different Outcomes for Canadian Youth?

Abstract: The findings suggest that participation in extracurricular activities, regardless of context, encourage positive youth development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
35
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 19 publications
4
35
0
4
Order By: Relevance
“…w, winter; s, summer activities and substance use risk behaviors as well as between OSP and substance use risk behaviors. 3,12,32 Our findings, after adjusting for covariates, were consistent for all measured substance use risk behaviors as OSP was significantly associated with decreased odds of both alcohol intoxication, cannabis use, smokeless tobacco use, and smoking. Some research supports our findings that athletes are less likely to smoke cigarettes or use cannabis, 19,32,33 while others show no associations between OSP and binge drinking.…”
Section: F I G U R E 1 Adjusted Odds Ratio (Or)supporting
confidence: 72%
See 2 more Smart Citations
“…w, winter; s, summer activities and substance use risk behaviors as well as between OSP and substance use risk behaviors. 3,12,32 Our findings, after adjusting for covariates, were consistent for all measured substance use risk behaviors as OSP was significantly associated with decreased odds of both alcohol intoxication, cannabis use, smokeless tobacco use, and smoking. Some research supports our findings that athletes are less likely to smoke cigarettes or use cannabis, 19,32,33 while others show no associations between OSP and binge drinking.…”
Section: F I G U R E 1 Adjusted Odds Ratio (Or)supporting
confidence: 72%
“…20 McCabe et al 3 recently demonstrated that sports participation was related to risky substance use (a composite measure combining binge drinking, getting drunk, and illegal drug use), and these findings are also consistent with other reports. 12,13,16,34 A longitudinal study by Wichstrom and Wichstrom 16 showed that adolescents initially involved in team sports had greater increases in alcohol intoxication, but lower increases in tobacco and cannabis use, during their adolescence and early adulthood compared with those involved in technical or strength sports. They also showed that participating in endurance sports, as opposed to technical or strength sports, predicted reduced growth in alcohol intoxication and tobacco use.…”
Section: F I G U R E 1 Adjusted Odds Ratio (Or)mentioning
confidence: 99%
See 1 more Smart Citation
“…Extracurricular creative activities at school and mathematics extracurricular activities at school are indicators of activities conducted in a school. Participation in extracurricular activities had resulted in positive and negative outcomes (Guèvremont, Findlay, & Kohen, 2014). Fiore (2015) reported that there was a weak relationship between mathematics extracurricular activities and math scores.…”
Section: Factors Predicting the Problem-solving Performance Differencesmentioning
confidence: 99%
“…Out-of-school-time programs frequently incur costs, generally covered by the out-of-school-time organization through grants or other revenues, and usually require transportation to be covered by the participants [8]. These factors may determine the feasibility of different social groups to embrace the participation of their children in out-of-school-time programs, in particular for low-income families who may not be able to afford participation in -or provide transportation to -out-ofschool activities.…”
mentioning
confidence: 99%